If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + y + 1 = 0 Reorder the terms: 1 + 6x + y = 0 Solving 1 + 6x + y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + 6x + -1 + y = 0 + -1 Reorder the terms: 1 + -1 + 6x + y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 6x + y = 0 + -1 6x + y = 0 + -1 Combine like terms: 0 + -1 = -1 6x + y = -1 Add '-1y' to each side of the equation. 6x + y + -1y = -1 + -1y Combine like terms: y + -1y = 0 6x + 0 = -1 + -1y 6x = -1 + -1y Divide each side by '6'. x = -0.1666666667 + -0.1666666667y Simplifying x = -0.1666666667 + -0.1666666667y
| 6+5=6 | | 7-(4x-3)=6-5x | | 3/2w-(-4/5) | | 4x+11=35+x | | 3(4x+8)=-8+20 | | 3x+y-2z= | | z+1=2z-7 | | F=295-2S | | 18x-19=15+2x | | 5(x+8)=30(x-2) | | 15x^2+3x-8=0 | | 9x=342 | | X^4+5x^3+4x^2-10x-12=0 | | 4x=x^2-110 | | x+(3x)+(6x-5)=180 | | 2x-15=4x+2 | | 2(6+2x)=8 | | 4x-3+7x=30 | | -7x-3y=9findslope | | 2(5x+3)=6x-6 | | 12x^3y^2-8xy^4-9x^2y/6x^2y^2 | | 2h+6(h+3)=-14 | | K^2=50-5k | | .33x+2=19 | | 1/4x-8=5/8x | | 9=5.5+x(10.5-5.5) | | 64x^2-48x+9=(8x-3) | | n^2+12n+19=-27 | | 0.50x+0.90x=0.80 | | -3(-4+3y)+5y=-8-(-12) | | 9p-8p=-3+11 | | 50x+90x=80 |